Clinical Profile and Conventional Risk Factors of Acute Coronary Syndrome in Late Elderly Patients - Simkhada, Rabindra; Khan, Barkadin; KC, Sanjay Singh (Nepalese Heart Journal, 2022)
Background and Aims: Acute coronary syndrome is an important health issue. There is paucity of its data in late elderly. We aimed to study their clinical profile and prevalence of conventional risk factors. Methods: Descriptive cross-sectional study conducted at Shahid Gangalal National Heart Centre from February 2022 to May 2022 including 71 consecutive patients of acute coronary syndrome of age >75 years. They were evaluated focusing their chief complaints and cardiovascular risk factors. Results: Mean age was 80.32±4.06 years. Forty (56.33%) were male and 31 (43.66%) were female. Thirty-nine (54.92%) were hypertensive, 29 (40.84%) were diabetic, 18 (25.35%) were smoker, 10 (14.08%) had history of dyslipidemia and 6 (8.45%) had family history of cardiovascular disease. Chest pain was present in 54 (76.05%), dyspnea in 28 (39.43%), sweating in 15 (21.12%) and nausea/vomiting in 8 (11.26%). Palpitation was present in 7 (9.85%), and epigastric pain in 13 (18.30%). Seven (9.85%) gave history of pre-syncope/ syncope and 6 (8.45%) had altered mental status. There was significant correlation of smoking (p=0.02) and types of ACS (p=0.001) with gender. Conclusion: Acute coronary syndrome were plausibility common in late elderly female. Chest pain was commonest complaint in both genders. Dyspnea, sweating and epigastric pain were also common. Pre-syncope/ syncope and altered mental status were also present in some cases. Conventional risk factors were quite common in both genders. These symptoms can be features acute coronary syndrome in elderly hence should be evaluated cautiously.